COMPETIÇÃO DE CULTIVARES DE GIRASSOL (Helianthus annuus L.) - Ungaro, Maria Regina G.; Toledo, Nilva Maria P. de; Gobbo, Carmem Renata L. S. (REVISTA DE AGRICULTURA, 2015)
COMPETIÇÃO DE CULTIVARES DE GIRASSOL (Helianthus annuus L.)